THE IMPACT OF THE WADAS ENVIRONMENTAL ISSUE ON GANJAR PRANOWO'S PRESIDENTIAL CANDIDACY - Noviansah, Gilang; Ardiansyah, Ardiansyah; Santoso, Edi (Jurusan Ilmu Komunkasi FISIP Universitas Jenderal Soedirman, 2024)
Abstract The national project for the construction of the Bener Dam has become controversial among environmental activists. The main cause is the mining of andesite stone as the main material for dam construction in Wadas Village. The mining is believed to damage the ecosystem and destroy the springs, which are the main source of the people's rice fields there. The conflict heated up when the Governor of Central Java, Ganjar Pranowo, issued a Location Determination Permit (IPL) for andesite mining, which included the Wadas area in it. Ganjar is considered a leader who is not pro-environmental preservation. The Wadas community uses social media as a means of resistance against government policies. After Ganjar Pranowo was appointed as a presidential candidate by the Indonesian Democratic Party of Struggle (PDIP), the issue of environmental damage was believed to be one of his political opponents weapons to damage the image of the Governor of Central Java. This study seeks to examine the negative sentiments that occur regarding the issue of environmental damage in Wadas a week after Ganjar Pranowo was declared a presidential candidate in 2024. This study uses a mix method with analysis from netlytic.org as the main material to see the response to the Wadas issue centered on Social Network Analysis (SNA) and the digital movement of Opinion. Keywords: Ganjar Pranowo, Twitter, Wadas Issues Abstrak Proyek nasional pembangunan Bendungan Bener menjadi pro kontra di kalangan pegiat lingkungan. Penyebab utamanya adalah penambangan batu andesit sebagai bahan utama material pembangunan bendungan yang dilakukan di Desa Wadas. Penambangan tersebut diyakini akan merusak ekosistem dan menghancurkan mata air yang menjadi sumber utama sawah-sawah masyarakat di sana. Konflik semakin memanas ketika Gubernur Jawa Tengah Ganjar Pranowo mengeluarkan Izin Penetapan Lokasi (IPL) penambangan batu andesit yang memasukan daerah Wadas di dalamnya. Ganjar dianggap sebagai pemimpin yang tidak pro terhadap pelestarian lingkungan. Masyarakat Wadas menggunakan media sosial sebagai alat perlawanan terhadap kebijakan pemerintah. Pasca ditetapkanya Ganjar Pranowo menjadi calon presiden oleh Partai Demokrasi Indonesia Perjuangan (PDIP), isu kerusakan lingkungan diyakini menjadi salah satu senjata lawan politiknya untuk merusak citra sang Gubernur Jawa Tengah tersebut. Penelitian ini berusaha mengkaji sentimen negatif yang terjadi terkait isu kerusakan lingkungan di Wadas seminggu setelah Ganjar Pranowo ditetapkan sebagai kandidat presiden 2024. Penelitian ini menggunakan mix method dengan analisis dari netlytic.org sebagai bahan utama melihat respon isu Wadas dengan berpusat pada Social Network Analysis (SNA) dan Digital Movement of Opinion. Kata kunci: Ganjar Pranowo, Twitter, Isu Wadas